PROGRAM PENINGKATAN PERAN CAREGIVER DALAM PERAWATAN SEDERHANA LUKA DIABETIC DI MASA PANDEMIC COVID-19 DI KOTA YOGYAKARTA - Wantonoro Wantonoro; Komarudin Komarudin; Dika Rizki Imania; Sigit Harun (Jurnal Abdi Insani, 2022)
The Province of the Special Region of Yogyakarta ranks third with the highest number of cases of Diabetes Mellitus (DM) nationally. One of the complications of DM, a severe health problem, is diabetic ulcers. Diabetic ulcer care and Covid-19 prevention are strictly associated with a high risk of transmission, a poor prognosis, and a high mortality rate when infected with Covid-19 are needed during a pandemic situation, one of which is to increase the role of the family (caregiver). The purpose of the activity is to optimize the role of caregivers in the simple care of diabetic wounds at home (stay at home) during the Covid-19 period. Comprehensive education about DM management in general and diabetic wounds in particular to families (caregivers), which is carried out using a direct method in conjunction with homecare services for simple treatment of diabetic ulcers while still implementing the Covid-19 health protocol. Providing good benefits to the family (caregiver) as evidenced by an increase in the average score of knowledge and also an increase in the average score of self-perception of ability in performing simple diabetic wound care. The development of long-term care for chronic patients can continue to be carried out by involving the active role of the family (caregiver) as the closest support system for patients. Education to the family directly increases the knowledge and confidence of the family in performing simple diabetic wound care. This program can be an alternative to optimizing infection prevention and the healing process of diabetic wounds.